Improving Low Vision through Bioptic Telescope: A Case Series: Poster Presentation - Case Series - Ophthalmologist - ADISTI LUKMAN (Majalah Oftalmologi Indonesia, 2023)
Introduction : Low vision (LV) is a condition when a person have binocular visual acuity of less than 6/18 to light perception, or a visual field of less than 10 degrees from the point of fixation, even after treatment and/or standard refractive correction. In Indonesia, it is known that the number of LV patients is around 4.8% of all blindness. Bioptics telescope is handsfree magnifying lenses, attached to the spectacles, used to enhance moderate to distant vision for patients with severely damaged eyesight. However, the use of this device is still uncommon in Indonesia. Case Illustration : Bioptic Telescope prescribed to 3 patients, adaptation time were less than 48 hours. The 1st patient, 11 years old male with chorioretinitis toxoplasmosis, initial visual acuity (VA) 6/60 both eyes improved to 6/18 both eyes, and able to write/type 30 words per minutes. The 2nd patient, 18 years old male with Familial Exudative Vitreoretinopathy, initial VA 1/60 Right Eye (RE) & 1/300 Left Eye (LE) improved to 6/18 RE, and able to write/type 10 words per 2 minutes. The 3rd patient, 25 years old female with congenital visual impairment, initial VA NLP RE & 6/60 LE improved to 6/24 LE, and able to write/type 20 words per minute. Discussion : Conclusion : This study reports the initial experience with bioptic telescope in low vision patients. This device proven to significantly increase visual acuity with short adaptation time and learning curve to watch, read, write, and type. The ability to escalate patient's quality of life makes bioptic telescope superior from other (hand-held) telescope